2019
DOI: 10.1016/j.jpurol.2019.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Immune expression in children with Wilms tumor: a pilot study

Abstract: BackgroundGiven improvements in multimodality therapy, survival among children with Wilms tumor (WT) exceeds 90%. However, 15% of children with favorable histology and 50% of children with anaplastic WT experience recurrence or progression. Of patients with advanced disease, only 50% survive to adulthood. In adult malignancies (including renal tumors), patient survival has improved with the advent of immunotherapy. However, little is known about the immune microenvironment of WT, making the potential role of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 41 publications
1
27
0
Order By: Relevance
“…Similar to other tumors, both adaptive and innate immune cells may infiltrate WT [38][39][40]. However, the relationship between such immune infiltrate and WT cells has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to other tumors, both adaptive and innate immune cells may infiltrate WT [38][39][40]. However, the relationship between such immune infiltrate and WT cells has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it must be considered that these factors are involved in the inhibition not only of NK cells, but also of other important effectors of anti-tumor response, including T cells and macrophages, that have been detected in the WT microenvironment, mostly confined in the stromal component of the tumor. [10][11][12] Thus, the use of novel therapies interfering with COX-2 and IDO activity may reveal a good strategy to unlock the immune response against WT.…”
Section: Discussionmentioning
confidence: 99%
“…The demonstration that activated NK cells can degranulate upon interaction with str-WT cells adds novel information about the important role that these effectors may play in the immune response against WT. Notably, it has been recently shown that NK cells are present in WT tissues in a significantly high percentage, 10 suggesting that NK cells can be recruited toward WT sites where they can mediate anti-tumor response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, not all children are cured and further research is warranted on enhancing the rate of therapeutic efficacy. Holl et al 40 analyzed the immune response of five patients with Wilms’ tumor before undergoing chemotherapy: activated CD8 and CD4 T cells infiltrated the tumor. This indicates that patients with Wilms’ tumor are susceptible to immunotherapy like specific adult malignancies.…”
Section: Discussionmentioning
confidence: 99%